PENINGKATAN PROFESIONALISME GURU SD MELALUI PELATIHAN PENULISAN KARYA TULIS - Ajang Rusmana; Widdy Sukma Nugraha; Neni Nadiroti Muslihah; Muhammad Nurjamaludin; Eko Fajar Suryaningrat (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2018)
Community service aims to provide insight into the knowledge of the work of professional development in elementary school teachers in Pameungpeuk Subdistrict, Garut, by providing insight into the importance of professional development work to improve professionalism for teachers, especially development work in the form of reporting class action research and scientific articles in the field accounting and education for teachers as well as providing the ability to develop works in the form of reporting class action research and scientific articles. The target of service is elementary / MI / equivalent teachers in Pameungpeuk Sub-District, Garut. Problems are solved in three stages of activities, namely preparation, implementation and evaluation. The results of the training show the level of success with an indication of the suitability of the material to the needs of elementary / MI / equivalent teachers, positive responses from participants, and most (75%) participants have understood the concept of professional work development, the importance of professional development work, the importance of improving the quality and quantity of professional development works in the form of class action reports and articles.